Carbon stocks under different land cover types in the Hallaydeghe wildlife reserve, northeastern Ethiopia - Grace DONDO; Sintayehu Workeneh DEJENE; Agnes UWIMBABAZI; Petros CHAVULA; Desta ANTENEH (Nova Geodesia)
The Hallaydeghe Wildlife Reserve, with its semi-arid to desert climate, features diverse land cover classifications. This study examined land cover changes and total carbon stocks from 1999 to 2019, focusing on forest, woodland, grassland, and bushland vegetation types. Land cover classes were created using 1999, 2003, and 2019 Landsat images. ArcGIS 10.4.1 and ERDAS IMAGINE were used for map creation, while future land use changes were simulated using the CA-Markov model. Carbon stock assessment involved five pools: soil, dead wood, aboveground, belowground, and litter carbon. Soil samples were collected at three depths, and data on woody plant species, soils, and litter were gathered through random systematic sampling. From 1999 to 2019, woodland grew by 57.94%, while grassland and bushland decreased by 6.86% and 10.51%, respectively. Projections for 2035 indicate a 40.68% increase in bushland, decreases in forest and grassland, and the emergence of bareland. Total carbon stocks varied among vegetation types: forest (35.94±6.63 tC ha-1), grassland (22.55±3.35 tC ha-1), and bushland (23.65±3.25 tC ha-1). The soil organic carbon pool contributed the most across all land cover categories. The shift from grassland to forest may impact the Grevy’s zebra’s habitat. Effective land use management is crucial for preserving carbon stores and ecosystem health. Implementing climate-smart policies, including community-based conservation and sustainable management practices, is essential to mitigate the impacts of land cover changes on wildlife and carbon stocks in the reserve.